Pre–post analysis of the impact of British Columbia nurse practitioner primary care clinics on patient health and care experience - Damien Contandriopoulos; Arnaud Duhoux; Katherine Bertoni; Gurprit K Randhawa (BMJ Open, 2023)
Objective This study aims to evaluate the impact of a primary care nurse practitioner (NP)-led clinic model piloted in British Columbia (Canada) on patients’ health and care experience.Design The study relies on a quasi-experimental longitudinal design based on a pre-and-post survey of patients receiving care in NP-led clinics. The prerostering survey (T0) was focused on patients’ health status and care experiences preceding being rostered to the NP clinic. One year later, patients were asked to complete a similar survey (T1) focused on the care experiences with the NP clinic.Setting To solve recurring problems related to poor primary care accessibility, British Columbia opened four pilot NP-led clinics in 2020. Each clinic has the equivalent of approximately six full-time NPs, four other clinicians plus support staff. Clinics are located in four cities ranging from urban to suburban.Participants Recruitment was conducted by the clinic’s clerical staff or by their care provider. A total of 437 usable T0 surveys and 254 matched and usable T1 surveys were collected.Primary outcome measures The survey instrument was focused on five core dimensions of patients’ primary care experience (accessibility, continuity, comprehensiveness, responsiveness and outcomes of care) as well as on the SF-12 Short-form Health Survey.Results Scores for all dimensions of patients’ primary care experience increased significantly: accessibility (T0=5.9, T1=7.9, p<0.001), continuity (T0=5.5, T1=8.8, p<0.001), comprehensiveness (T0=5.6, T1=8.4, p<0.001), responsiveness (T0=7.2, T1=9.5, p<0.001), outcomes of care (T0=5.0, T1=8.3, p<0.001). SF-12 Physical health T-scores also rose significantly (T0=44.8, T1=47.6, p<0.001) but no changes we found in the mental health T scores (T0=45.8, T1=46.3 p=0.709).Conclusions Our results suggest that the NP-led primary care model studied here likely constitutes an effective approach to improve primary care accessibility and quality.